Tariffs and welfare: A common, invalid anti-tariff argument - Sweeney, Richard J. (Economics and Business Review, 2023)
President Trump imposed tariffs in 2017 on several of China’s exports, notably steel. Many papers opposed these tariffs by using a common, invalid argument: rather than arguing these tariffs reduced U.S. welfare, they argue U.S. consumers and businesses pay the tariffs, a different, rhetorical issue. Their main evidence of harm is increases in imported goods’ after-tariff U.S. prices, especially relative to other goods’ U.S. prices. In a standard, small general equilibrium model (two countries, two goods, two factors), this price evidence is wholly ambiguous—it is even consistent with the view that Trump’s tariff was optimal, increasing U.S. welfare. Even sophisticated papers are similarly ambiguous. All fail because they neglect how government uses tariff revenue. Relying on fallacious arguments makes the free-trade position look weak and encourages protectionism.